Organizational Culture and Lecturer Creativity in the Development of Student Organizational Citizenship Behavior - Griet Helena Laihad; Purnama Pasande (STAI Hubbulwathan Duri, 2023)
Management researchers have established a connection between Organisational Citizenship Behaviour (OCB) and individual achievement in organisational environments. However, there is a limited number of studies that specifically focus on OCB among college and university students. This study aims to investigate the phenomenon of Organisational Citizenship Behaviour (OCB) among undergraduate college students. Specifically, it explores how organisational culture and lecturer's inventiveness influence students' OCB in the college setting. A total of 104 students from a private College in Luwuk Banggai were surveyed to gather data. The technique of data analysis using regression analysis and Structural Equation Modelling (SEM). The findings suggest that the organisational culture, characterised by a focus on details, and the lecturer's creativity, characterised by flexible and spontaneous thinking, have the greatest impact on students' organisational citizenship behaviour (OCB) in terms of their initiative, within the college setting. Thus, it can be inferred that when fostering students' Organisational Citizenship Behaviour (OCB), it is important to consider both the organisational culture and the creativity of the lecturers.